Virginia’s natural conditions as a war site during the US independence struggle in 1780–1781 - Stelmasiak, Katarzyna (Armia kontra natura, 2020)
This article presents the natural environment of Virginia and shows how it affected the military operations during the American revolution. Notes on the state of Virginia by Thomas Jefferson served as the source for describing the natural conditions of the state. Geographically, Virginia is an extremely privileged land. Beautifully situated on the Chesapeake Bay has a varied landscape. There are plains along the coast, and inland the surface is highland – mountainous. There are numerous rivers, and the largest of them – James and Potomac are considered deep estuaries to the Chesapeake Bay.Because of the terrain and a small settlement, the war in Virginia took on a different character than in New England. Compact and maneuverable army of Lord Charles Cornwallis applied fast maneuvers. At the head of their way to attack, the English set gunners, and the artillery assigned an independent function. The strength of the cavalry was also appreciated, both in attack and in retreat. In turn, on the American side, the main burden of defense rested on militia troops.The first war operations took place in Virginia in the autumn of 1780, but the actual offensive began in the spring of 1781. The British occupied the state capital of Richmond, and Lord Cornwallis made a bold attempt to capture Governor Thomas Jefferson and some more important members of the state assembly. By a lucky coincidence, the Virginia government and legislature were warned of imminent danger, and Jefferson was escaping from his Monticello estate near Charlottesville, Central Virginia, 5 minutes before the English arrived.The decisive battle took place at Yorktown. The French and American armies reached Virginia by land and sea in early September 1781, and faced Lord Cornwallis at twice his strength. The cornered and attacked Lord Cornwallis capitulated on October 19th. After the surrender, the hostilities ceased and the English declared themselves defeated in the US Revolutionary War.